Short Term Outcome of Fixation of Isolated Avulsion Fractures of Posterior Cruciate Ligament; Case Series (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACTObjective: To evaluate the outcome of isolated posterior cruciate ligament avulsion injuries after open reduction and screw fixation in our setup.Methods: This was a prospective observational cross sectional study conducted during January 2012 to July 2015. Performa was made which comprises of bio-data, mechanism of injury, pre-operative x-rays, MRI, classification and physical examination. Patients who had isolated posterior cruciate ligament avulsion injury with bony fragment of around 1cm, they underwent open reduction and screw fixation included in this study. Short-term outcome assessment was carried out at 6 months in terms of stability, range of motion achieved using Lysholm knee scores. Patient between 20-35 years of age included in the study. All patient underwent fixation through 4.5 cannulated screw along with washer.Results: There were total 5 patients who presented with isolated PCL injuries. Motor vehicle trauma was found in 4 patients and 1 patient had sports related injury. Type III fractures were found in 4 patients and while the remaining 1 patient had type II fracture. Postoperatively all the patients had improved posterior drawer test, and radiological examination showed complete healing. There were no wound infections and 1 patient developed hypertrophic scar and 3 patients developed knee swelling which was resolved with compression bandages and continuous physiotherapy.Conclusions: Early operative intervention of isolated posterior cruciate ligament avulsion fractures achieves better stability and optimal results with few complications. Further studies are warranted in this regard.